A Novel One-Pot Synthesis, Characterization, DNA Binding and Cleavage Studies on bis(Phenylhydrazoneglyoxylato)diaqua Metal(II) Complexes - Pradeep, R.; Sivasankar, B.N. (Asian Journal of Chemistry, 2018)
Phenylhydrazoneglyoxylic acid, C6H5NHN=CHCOOH, formed in situ by the aqueous condensation between phenyl hydrazine and glyoxylic acid, in the presence of metal ions such as Mn(II), Co(II), Ni(II), Cu(II), Zn(II) and Cd(II) yielded water insoluble bis(phenylhydrazoneglyoxylato)diaqua metal(II) complexes. These complexes were characterized by analytical, spectral (UV-visible, IR and NMR) and thermal techniques. Infrared, NMR and X-ray powder diffraction patterns reveal the formation and isomorphic nature of [M(OOCCH=NNHC6H5)2(H2O)2] complexes. Thermal degradation studies show multi-step degradation behaviour and the final weight losses are in accordance with the formation of respective metal oxides as end residues. Octahedral geometry around the metal ion has been proposed on the basis of spectral and thermal studies. The interaction of the complexes with calf thymus-DNA (ctDNA) has been explored by absorption titration method which revealed that the compounds could interact with ctDNA through electrostatic interaction. The gel electrophoresis assay demonstrated the zinc complex exhibit good cleavage efficiency, which is concentration dependent.